Anthropometric and biochemical correlates of PAPP-A2, free IGF-I, and IGFBP-3 in childhood. Issue 3 (March 2020) - Fujimoto, Masanobu; Khoury, Jane C; Khoury, Philip R; Kalra, Bhanu; Kumar, Ajay; Sluss, Patrick; Oxvig, Claus; Hwa, Vivian; Dauber, Andrew
Abstract : Objective: Pregnancy-associated plasma protein-A2 (PAPP-A2) is a metalloproteinase that cleaves IGFBP-3 and IGFBP-5. Human mutations in PAPPA2 result in short stature with a low percentage of free IGF-I. Little is known about PAPP-A2 levels and the regulation of free IGF-I throughout childhood. We examined PAPP-A2 and intact IGFBP-3 levels in childhood and explored associations between PAPP-A2, free and total IGF-I, and total and intact IGFBP-3 and their relationship to the percentage of free to total IGF-I and anthropometric factors. Design: Cross-sectional study at a single center. Methods: PAPP-A2, free IGF-I, and intact IGFBP-3 levels were measured in childhood (3–18 years old) and an evaluation of the relationship between these proteins and anthropometric factors. Results: In 838 children, PAPP-A2 consistently decreased throughout childhood. In contrast, free IGF-I increased. A pubertal peak in free IGF-I was present in females but was less evident in males. Intact and total IGFBP-3 increased throughout childhood; however, intact IGFBP-3 had a more marked rise than total IGFBP-3. Percent free IGF-I decreased with no distinct pubertal peak. PAPP-A2 levels positively correlated with the percent free IGF-I (Male, Female; r = 0.18, 0.38; P < 0.001) and negatively with intact IGFBP-3 (Male, Female; r = −0.58, −0.65; P < 0.0001). Conclusions: This is the first study to describe serum PAPP-A2 and intact IGFBP-3 in children between 3 and 18 years of age. Our correlative findings suggest that PAPP-A2 is an important regulator of the percent free IGF-I which can be a marker of perturbations in the GH/IGF-I axis.